Report respecting the Applications to the Treasury on the subject of Treasure-Trove (Proceedings of the Society of Antiquaries of Scotland, 1862)
The Secretary provided an update and some of the correspondence with regards to the Society's petition to alter the Treasure Trove laws (see Rhind, p.76).